Improving Studentsâ vocabulary Mastery By Using Blended Learning Model in State Polytechnic Padang - damaiyanti, muthia; Sari, Indah (Script Journal: Journal of Linguistic and English Teaching, 2017)
The research aims at improving the vocabulary mastery of students at Padangâs State Polytechnics for the 2015/2016 academic year by applying a blended learning model. Blended learning is an interactive learning model which combines face-to-faceÂ  with web-based learning. Vocabulary is a vital sub-skill in mastering a language and thus a suitable topic for a classroom action research (CAR). . The CAR theory applied is by Kemmis, S and McTaggart (2005) and the Blended Learning theory used is by Bersin (2004). The instruments are test, observation, field note and interview. Quantitative data are collected by a test result in which it is used to see how the studentâs vocabulary mastery progresses after applying the blended learning model. Qualitative data gathered included observation, field note and interview analyzed descriptively in order to find out the factors affecting studentâs vocabulary mastery by implementing blendedÂ Â